2014
DOI: 10.1097/pcc.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Neutrophil Gelatinase–Associated Lipocalin Predicts Acute Kidney Injury After Pediatric Cardiac Surgery*

Abstract: Urine neutrophil gelatinase-associated lipocalin is a predictive biomarker for acute kidney injury after pediatric cardiac surgery, and it may permit earlier intervention that improves outcome of acute kidney injury. Urine neutrophil gelatinase-associated lipocalin normalized to urine creatinine improves the prediction of acute kidney injury severity but offers no advantage in acute kidney injury diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
21
2
1
Order By: Relevance
“…It is important to distinguish these novel AKI biomarkers from functional biomarkers such as serum creatinine and cystatin C. Novel biomarkers classically include those that detect damage; some of these include urine neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), interleukin 18 (IL-18), liver fatty acid binding protein, and others [26]. These have been extensively studied in children undergoing congenital heart surgery and cardiopulmonary bypass [27][28][29]. In these studies, the biomarkers rose between 2 and 12 h after cardiopulmonary bypass and successfully predicted AKI, as defined by rise in serum creatinine, at 48 h following surgery [27].…”
Section: Advances In Novel Biomarkers: Moving Beyond Serum Creatininementioning
confidence: 99%
“…It is important to distinguish these novel AKI biomarkers from functional biomarkers such as serum creatinine and cystatin C. Novel biomarkers classically include those that detect damage; some of these include urine neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), interleukin 18 (IL-18), liver fatty acid binding protein, and others [26]. These have been extensively studied in children undergoing congenital heart surgery and cardiopulmonary bypass [27][28][29]. In these studies, the biomarkers rose between 2 and 12 h after cardiopulmonary bypass and successfully predicted AKI, as defined by rise in serum creatinine, at 48 h following surgery [27].…”
Section: Advances In Novel Biomarkers: Moving Beyond Serum Creatininementioning
confidence: 99%
“…Most of the paediatric cardiac surgery-associated acute kidney injury reports note much longer cardiopulmonary bypass times and higher average neutrophil gelatinase-associated lipocalin values in patients developing acute kidney injury compared with ours. [27][28][29][30]33,34 Prolonged surgery with cardiopulmonary bypass times comparatively longer than those in our study may accentuate these processes leading to acute kidney injury. Our study was unique in that patients in the acute kidney injury and non-acute kidney injury group showed equal median cardiopulmonary bypass times.…”
Section: Cpbmentioning
confidence: 61%
“…24,29 Adding urinary neutrophil gelatinase-associated lipocalin to these models increased the area under the curve value by a small extent. 25,30 For example, in one study the area under the curve of 0.85 for prediction of acute kidney injury by the clinical model was increased to 0.91 by adding urinary neutrophil gelatinase-associated lipocalin. 30 Further, in our study, the kinetics of urinary and plasma neutrophil gelatinase-associated lipocalin values differed with plasma neutrophil gelatinaseassociated lipocalin values showing a later peak.…”
Section: Cpbmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have supported the hypothesis that duration bears a negative impact on postoperative renal function. 2,[5][6][7]18,19,20,22,23 Sethi et al reported that duration of CPB >90 minutes could cause AKI in adults. 24 Similarly, Zheng et al reported that AKI was significantly more common in patients with duration of CPB >90 minutes.…”
Section: Discussionmentioning
confidence: 99%